2013
DOI: 10.1515/bot-2012-0200
|View full text |Cite
|
Sign up to set email alerts
|

Use of Posidonia oceanica seedlings from beach-cast fruits for seagrass planting

Abstract: Posidonia oceanica seedlings produced from beach-cast fruits were planted in an area where this Mediterranean seagrass was lost as a consequence of fishfarming. The effects of substratum type (dead matte vs. meadow) and planting level (above vs. below bottom surface) on seedling survivorship and leaf development were evaluated after 3 years. Seedling capacity to resist uprooting was also tested by comparing survivorship and leaf development after 2 years in seedlings firmly anchored in dead matte by artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…For seeds, light limitation imposed by mature meadows controls P. oceanica leaf self-shading and plant competition with its own recruits while also promoting increased seedling survival rates in open, uncolonized areas where clonal growth is limited. As stated by Terrados et al (2013), seedlings planted inside a P. oceanica meadow led to complete mortality after 3 years, while seedlings planted in a dead meadow presented a survival rate of 44% during the same time frame. Shading was suggested as the process driving mortality, a conclusion which supports the results of the present study.…”
Section: Discussionmentioning
confidence: 69%
“…For seeds, light limitation imposed by mature meadows controls P. oceanica leaf self-shading and plant competition with its own recruits while also promoting increased seedling survival rates in open, uncolonized areas where clonal growth is limited. As stated by Terrados et al (2013), seedlings planted inside a P. oceanica meadow led to complete mortality after 3 years, while seedlings planted in a dead meadow presented a survival rate of 44% during the same time frame. Shading was suggested as the process driving mortality, a conclusion which supports the results of the present study.…”
Section: Discussionmentioning
confidence: 69%
“…The transplant area was located on a seabed dominated by dead matte structures (Tomasello et al, 2009b) (Fig. 6), as some studies have shown that matte is a particularly suitable substratum for planting seagrass (Di Maida et al, 2013;Terrados et al, 2013).. Establishment showed a decreasing trend during the first 3 years of monitoring, followed by stationary values of about 32% in the final three years, while cuttings de-tached from the grids showed the opposite trend, reaching a final value of 61% (Fig.…”
Section: Transplantation In the Gulf Of Palermo Monitoring Resultsmentioning
confidence: 99%
“…Since the 1970s, restoration with P. oceanica in the Mediterranean Sea has been carried out to assess various transplanting and seedling techniques. Transplant success was found to be influenced by the nature of the substratum, with dead matte habitat showing higher survival and growth rates than sand, pebble and rock (Terrados et al, 2013). Also, horizontal rhizomes showed higher survival and growth rates than their vertical counterparts (Molenaar et al, 1993;Piazzi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dead matte results the most suitable substratum for P. oceanica planting (Di Maida & al. 2013;Terrados & al. 2013).…”
Section: Management and Restoration Strategiesmentioning
confidence: 99%